Hypercellular bone marrow in aplastic anemia: A case report of two patients - Ryan Sweeney (Wiley, 2021)
Abstract Aplastic anemia is a disorder of bone marrow failure characterized by a hypocellular bone marrow. We report two cases with an initial hypercellular bone marrow at the time of presentation, suggesting a new phase in the pathogenesis of the disease.